L’inscription de l’équitation de tradition française à l’UNESCO - Sylvie Grenet (In Situ)
At the end of 2011, the "equitation in the French tradition" was inscribed on the UNESCO representative list of intangible cultural heritage. This article aims at presenting the long history of the project, its content, and its issues.